Computer Aided Modelling and Performance Prediction of Fertiliser Solar Pond for Agricultural Operations - Murthy, G.R Ramakrishna; Naik, R; Pandey, K P (Journal of Agricultural Engineering, 2007)
Performance prediction of a new salt like fertiliser is crucial before it is used in a large solar pond. The heat transfer process in solar pond is modelled and implemented through a computer program for assessing the thermal performance in terms of temperature of lower convective zone (LCZ). The programmed model is validated using the real time data of a working solar pond. The model is found to be in good agreement with the observed data. The program is tested for predicting the solar pond performance using a fertiliser salt, Muriate of Potash. The solar pond is observed to attain steady state after 10th month of pond operation. The pond started in April attained peak LCZ temperatures quicker than that started in January. The pond behavior is well explained by superimposing temperature surface and contours.